Local Governance and Post-Conflict Societies and Diversity Management : international and political journal - Ibrahim, Prof. Dr. Nazem Nawaf; Ibrahim , Haitham Ayad (The International and Political Journal, 2024)
Countries face recurring crises, as our era is described as the era of crises. As a result, countries are looking for immediate and permanent solutions to these crises, such as the crisis of managing post-conflict societies by implementing political, economic and social reforms that mitigate and eliminate societal conflict. The components of diverse societies have material and moral demands, and these demands are often met with non-peaceful methods and mechanisms, such as ethnic cleansing. This research attempts to demonstrate the possibility of local administration as a peaceful mechanism for managing the diversity file and as a political and legal treatment among the treatments for the effects of societal conflict in post-conflict societies.